Climate change induced rainfall patterns affect wheat productivity and agroecosystem functioning dependent on soil types. Issue 2 (23rd January 2016) - Tataw, James Tabi; Baier, Fabian; Krottenthaler, Florian; Pachler, Bernadette; Schwaiger, Elisabeth; Wyhlidal, Stefan; Formayer, Herbert; Hösch, Johannes; Baumgarten, Andreas; Zaller, Johann G.
Abstract: Wheat is a crop of global importance that supplies carbohydrates to more than half of the worlds' population. We examined whether climate change‐induced rainfall patterns, which are expected to produce less frequent but heavier rain events, will alter the productivity of wheat and agroecosystem functioning on three different soil types. Therefore, in a full‐factorial experiment, Triticum aestivum L. was cultivated in 3‐m 2 lysimeter plots, each of which contained one of the following soil types: sandy calcaric phaeozem, gleyic phaeozem and calcic chernozem. Predicted rainfall patterns based on the calculations of a regionalised climate change model were compared with the current long‐term rainfall patterns, and each treatment combination was replicated three times. Future rainfall patterns significantly reduced wheat yield, leaf area index, and plant height at the earlier growth stages; it equally decreased the arbuscular mycorrhizal fungi colonisation of roots and increased the stable carbon isotope signature (δ 13 C) of wheat leaves. Sandy soils with inherently lower mineralization potential negatively affected wheat growth, harvest index, and yield but stimulated early season root production. The interaction between rainfall and soil type was significant for the harvest index and early wheat development. Our results suggest that changes in rainfall intensity and frequency can significantly affect the functioning of wheat agroecosystems. Wheat production under future rainfall conditions will likely become more challenging as further concurrent climate change factors become prevalent.